Percutaneous Management of Posttransplant Biliary Complications - Mitchell, Jason W.; Maduabia, Arthur I.; Cristescu, Mircea; Peters, Gail L. (Digestive Disease Interventions, 2019)
Interventional radiology plays a major role in the management of posttransplant biliary complications. This review aims to discuss biliary complications of liver transplantation and will outline the role of interventional radiology, diagnosis, and management of these problems.
Keywords: liver transplant; complications; interventional radiology